AUDIT OPERASIONAL TERKAIT HAZARD AND DISASTER EVENT RISKPADA SIKLUS PRODUKSI INDUSTRI KELAPA SAWIT “X” DI SURABAYA - Karina Dewi Indianti; Adhicipta Raharja Wirawan (Perpustakaan Universitas Surabaya, 2018)
PT.X engaged in the palm oil industry in Surabaya City, employs over 1000 employees and has a high risk of danger in its production process. Therefore, research about operational audits related to hazard and disaster event risk is necessary to evaluate the Occupational Health and Safety Management System applied by PT.X. The audit process to be performed on PT.X is related to the occupational health and safety management system applied by the company in the production cycle. The method that will be used to perform the data settlement is by conducting interviews, observation, and document analysis. PT.X has implemented a Occupational Health and Safety Management System in its company but for 8 years the system has been applied, the company has never reached the goal of implementation of Occupational Health and Safety Management System that is achieved